Effectiveness and safety of recombinant human bone morphogenetic protein-2 for adults with lumbar spine pseudarthrosis following spinal fusion surgery: A systematic review. Issue 4 (April 2016) - Bodalia, P. N.; Balaji, V.; Kaila, R.; Wilson, L.
Abstract : Objectives: We performed a systematic review of the literature to determine the safety and efficacy of bone morphogenetic protein (BMP) compared with bone graft when used specifically for revision spinal fusion surgery secondary to pseudarthrosis. Methods: The MEDLINE, EMBASE and Cochrane Library databases were searched using defined search terms. The primary outcome measure was spinal fusion, assessed as success or failure in accordance with radiograph, MRI or CT scan review at 24-month follow-up. The secondary outcome measure was time to fusion. Results: A total of six studies (three prospective and three retrospective) reporting on the use of BMP2 met the inclusion criteria (203 patients). Of these, four provided a comparison of BMP2 and bone graft whereas the other two solely investigated the use of BMP2. The primary outcome was seen in 92.3% (108/117) of patients following surgery with BMP2. Although none of the studies showed superiority of BMP2 to bone graft for fusion, its use was associated with a statistically quicker time to achieving fusion. BMP2 did not appear to increase the risk of complication. Conclusion: The use of BMP2 is both safe and effective within the revision setting, ideally in cases where bone graft is unavailable or undesirable. Further research is required to define its optimum role. Cite this article: Mr P. Bodalia. Effectiveness and safety of recombinant human bone morphogenetic protein-2 for adults with lumbar spine pseudarthrosis following spinal fusion surgery: A systematic review. Bone Joint Res 2016;5:145–152. DOI: 10.1302/2046-3758.54.2000418.